Abnormal Return dan Volume Perdagangan Saham atas Peristiwa Pencemaran Lingkungan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - M.Muhayin A Sidik; Umarudin Kurniawan (Jurnal Ilmiah ESAI, 2020)
This study aims to examine the abnormal return and stock trading volume to environmental pollution events. This research is included in quantitative research. Data source in this research is secondary data. Sources of data in this study were obtained from the 3 most trusted online mass media, namely; Kompas, Republika and Koran Tempo to find information about environmental pollution events conducted by the company, as well as for financial data of share price and trading volume through Indonesia Stock Exchange website or other providers such as, yahoo finance and World Investment. Based on the test results, it can be concluded that, the hypothesis stating that there is a market reaction to environmental contamination events indicated by the decrease in average abnormal return before and after the reporting of environmental pollution events conducted by companies listed on the Indonesia Stock Exchange was rejected, The difference in market reaction to environmental contamination events is indicated by the decrease in average abnormal return after the reporting of environmental pollution events conducted by companies listed on the Indonesia Stock Exchange. The second hypothesis is rejected, the hypothesis that there is a market reaction to environmental contamination events is indicated by a decrease in average trading volume before and after the reporting of environmental pollution events conducted by companies listed on the Indonesia Stock Exchange, there is no market reaction to the event of environmental contamination Which is indicated by a decrease in average trading volume after the reporting of environmental pollution events conducted by companies listed on the Indonesia Stock Exchange.